Proactive personality, burnout, and teaching enjoyment: exploring relationships in Chinese English teachers - Chunyan, Hu; Ying, Liao (Frontiers in Psychology, 2024)
This study examines the relationships between proactive personality, burnout, and teaching enjoyment among Chinese English as a Foreign Language (EFL) teachers. The research aims to clarify how proactive personality traits relate to teaching enjoyment and burnout and to explore their interactions in the context of EFL instruction.The study included a sample of 420 Chinese EFL teachers, and Structural Equation Modeling (SEM) was used to assess the relationships among proactive personality, burnout, and teaching enjoyment. Data underwent detailed statistical analysis to identify both direct and mediating effects within the proposed model.The findings from the SEM analysis revealed significant direct relationships between proactive personality, burnout, and teaching enjoyment among Chinese EFL educators. Proactive personality was associated with a decrease in burnout (β = -.366, SE = .159, p < .001). For every unit increase in proactive personality, teachers reported experiencing higher levels of teaching enjoyment (β = .487, SE = .176, p < .001). Teaching enjoyment, in turn, was a significant mediator in the relationship between proactive personality and burnout (β = -.249, SE = .102, p < .001). These findings suggest that proactive personality is positively associated with teaching enjoyment, which, in turn, may relate to lower levels of burnout among EFL teachers.Discussion: This study highlights the importance of proactive personality traits in enhancing teaching enjoyment and reducing burnout among Chinese EFL teachers. The findings emphasize how proactive tendencies contribute to teachers' well-being, professional satisfaction, and, ultimately, the quality of EFL instruction. These results suggest practical applications, such as developing interventions that encourage proactive traits and increase teaching enjoyment among EFL educators, which may improve the educational experience for EFL students.